Pengaruh Kepercayaan Produk, Interaktivitas Produk Terhadap Keputusan Pembelian Melalui Brand Image Sebagai Variabel Mediator - Rafika Dewi; Muniroh Muniroh (MES Bogor, 2026)
The phenomenon of increasing competition in the skincare industry, particularly with the Skintific brand, requires companies to build consumer trust and create effective interactions to enhance brand image and encourage purchasing decisions. This research uses a quantitative approach with a survey method. The sample for this study consists of 125 respondents who are users of Skintific skincare products obtained through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results of the study indicate that product trust and product interactivity have a positive and significant effect on brand image. Additionally, brand image has a significant effect on purchasing decisions and can mediate the influence of product trust and product interactivity on purchasing decisions. These findings provide implications for skincare brand marketing strategies to focus more on building trust and strong interaction with consumers in order to strengthen brand image and drive purchasing decisions.